2019
DOI: 10.1042/bcj20180381
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol-3-phosphate acyltransferases 3 and 4 direct glycerolipid synthesis and affect functionality in activated macrophages

Abstract: Macrophage classical M1 activation via TLR4 triggers a variety of responses to achieve the elimination of foreign pathogens. During this process, there is also an increase in lipid droplets which contain large quantities of triacylglycerol (TAG) and phospholipid (PL). The functional consequences of this increment in lipid mass are poorly understood. Here, we studied the contribution of glycerolipid synthesis to lipid accumulation, focusing specifically on the first and rate-limiting enzyme of the pathway: glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…We showed that intracellular localization of M. leprae to lipid droplets was clearly reduced in GPAT3 KO cells compared to wild-type cells. This observation is in agreement with a recent study showing that in bone marrow-derived macrophages from Gpat3 -/mice, not only was the formation of Kdo 2 -lipid A (KLA)-inducible lipid droplets suppressed, intriguingly, the phagocytic capacity of the macrophages was also reduced [42]. In the present study, however, we have clearly shown that GPAT3 does not affect the ability of THP-1 cells to undergo phagocytosis.…”
Section: Discussionsupporting
confidence: 94%
“…We showed that intracellular localization of M. leprae to lipid droplets was clearly reduced in GPAT3 KO cells compared to wild-type cells. This observation is in agreement with a recent study showing that in bone marrow-derived macrophages from Gpat3 -/mice, not only was the formation of Kdo 2 -lipid A (KLA)-inducible lipid droplets suppressed, intriguingly, the phagocytic capacity of the macrophages was also reduced [42]. In the present study, however, we have clearly shown that GPAT3 does not affect the ability of THP-1 cells to undergo phagocytosis.…”
Section: Discussionsupporting
confidence: 94%
“…We observed that M1-like activation of siCon cells led to an increase in Cer d18:1/24:1, Cer d18:1/24:0 (Figure 3B) and TAG (Figure 3C) levels, which were consistent with previous reports for TAGs [12] and Cer [42]. Remarkably, FATP4 KD further elevated the levels of TAGs and Cer d18:1/24:1.…”
Section: Significant Changes Of Gpls Spls and Tags In M1 And M2 States By Fatp4 Inactivation In Thp-1supporting
confidence: 92%
“…Specifically, FATP4 inactivation induces a metabolic shift from GPLs and Cer towards TAGs as reported in skin fibroblasts [27] and skin [21,22] of Fatp4-null mice as well as in subcutaneous fat of adipose-specific Fatp4-deficient mice fed with high-fat diet [30]. As GPLs, SPLs, and TAGs are critical for macrophage functions [9][10][11][12][13][14], we hypothesized that FATP4 inactivation may affect the cytokine release by altering these lipids. Because of FATP4 localization in the ER [25,26], we chose a stress model which involves unfolded protein response (UPR) activation in the ER [31] in two in vitro systems using small interfering RNA (siRNA) against FATP4 in THP-1-derived macrophages and BMDMs of myeloid-specific Fatp4-deficient (Fatp4 M-/-) mice.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, efficient phagocytosis depends on lipolysis ( Chandak et al, 2010 ). Thus, it is well conceivable that mammalian macrophages lacking GPAT3 or GPAT4 show compromised phagocytosis ( Quiroga et al, 2019 ). In Dictyostelium , however, phagocytosis does not seem to depend on a TAG reservoir, because in gpat − mutants phagocytosis is even increased, whether or not the cells are challenged with palmitic acid ( Fig.…”
Section: Discussionmentioning
confidence: 99%